HDL cholesterol efflux capacity and cholesteryl ester transfer are associated with body mass, but are not changed by diet-induced weight loss: A randomized trial in abdominally obese men. (July 2018) - Talbot, Charlotte P.J.; Plat, Jogchum; Joris, Peter J.; Konings, Maurice; Kusters, Yvo H.A.M.; Schalkwijk, Casper G.; Ritsch, Andreas; Mensink, Ronald P.
Abstract: Background and aims: Obesity is associated with a lower HDL-mediated cholesterol efflux from macrophages and a higher CETP (cholesteryl ester transfer protein) activity, but effects of weight loss are not clear. In addition, associations with visceral and subcutaneous adipose tissue are not known. We therefore investigated effects of diet-induced weight loss on HDL-mediated cholesterol efflux and cholesterol ester (CE) transfer in abdominally obese men. Differences between normal-weight and abdominally obese men were also examined. Methods: Twenty-five apparently healthy, normal-weight men (waist circumference: <94 cm) and 52 abdominally obese men (waist circumference: 102–110 cm) were included. Abdominally obese subjects were randomly allocated to a dietary weight-loss intervention group or a no–weight loss control group. Individuals from the intervention group followed a very-low-calorie diet for 6 weeks to obtain a waist circumference below 102 cm, followed by a 2-week weight-stable period. Cholesterol efflux was measured in BODIPY-labeled murine J774 macrophages. CE transfer was measured by quantifying the transfer of CE from radiolabeled exogenous HDL to apoB-containing lipoproteins. Results: Cholesterol efflux capacity was 9 percentage point (pp) lower in abdominally obese than in normal-weight men ( p ≤0.001), while CE transfer was 5 pp higher ( p ≤0.01). Diet-induced weight-loss of 10.3 kg did not change cholesterol efflux and CE transfer. In addition, stepwise regression analysis did not suggest that the different fat depots are differently related to efflux capacity and CE transfer. Conclusions: After a 2-week weight-stable period, dietary weight loss of 10 kg did not improve ABCA1-mediated cholesterol efflux and CE transfer in abdominally obese men. Highlights: ABCA1-mediated cholesterol efflux (CE) and CETP activity are associated with BMI. The various fat depots are not differently related to CE and CETP activity. CE and CETP activity are not changed by diet-induced weight loss of 10 kg. Two weeks of weight stable may be too short to observed effects on these parameters.